Percutaneous Renal Biopsy: Comparison of Blind and Real-time Ultrasound Guided Technique - Pokhrel, Anil; Agrawal, Rajendra Kumar; Baral, Anil; Rajbhandari, Ajaya; Hada, Rajani (Journal of Nepal Health Research Council, 2018)
Background: Percutaneous renal biopsy is performed for diagnosis and prediction of prognosis of renal diseases. Adequacy of tissue and clinically significant bleeding are the main issues of the procedure. We aimed to compare these issues in renal biopsy by blind and real time ultrasound guided technique.Methods: It was a cross sectional, randomized study conducted between June 2016 to December 2016. In blind technique, marking for biopsy was done by ultrasound. Two attempts were performed for all and more if tissue was inadequate. Patients kept in bed rest for 24 hours, observed for post procedure hematuria and ultrasound done at 6 hours and 24 hours to diagnose perinephric hematoma.Results: Total 75 biopsies (blind = 37 and Ultrasound -guided = 38) were evaluated. Blind and Ultrasound-guided technique had significant difference of number of attempt (mean±SD) 2.4±0.6 and 2.1±0.3 (p